Tax Competition and its Consequences for Tax Revenue Structure in Developed Countries: Empirical Evidence Using Panel Cointegration Approach - Ján Huňady; Marta Orviská (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2015)
The paper examines the long run changes in the tax revenue structure in developed countries. We are particularly focused on the testing of a potential shift from taxation on mobile tax bases to less mobile ones, which could be seen as one of the results of rising tax competition. We assume that a decrease in corporate tax revenues is compensated for by higher tax revenues from taxing work and property. Our dataset consists of panel date from 22 OECD countries within the period 1965 to 2012. We tested the potential causalities within the tax mix using Granger causality tests as well as the DOLS and FMOLS panel cointegration techniques in order to reveal possible long run causalities. As far as we know, these techniques have not before been used in this field. Long-run inverse causalities between corporate tax and personal tax revenue as well as corporate tax revenue and indirect taxes are found. Our results could have several important implications for the tax policies in developed countries.